2019
DOI: 10.1038/s41467-019-09037-9
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal bacterial proteolytic activity determines sensitivity to dietary antigen through protease-activated receptor-2

Abstract: Microbe-host interactions are generally homeostatic, but when dysfunctional, they can incite food sensitivities and chronic diseases. Celiac disease (CeD) is a food sensitivity characterized by a breakdown of oral tolerance to gluten proteins in genetically predisposed individuals, although the underlying mechanisms are incompletely understood. Here we show that duodenal biopsies from patients with active CeD have increased proteolytic activity against gluten substrates that correlates with increased Proteobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 67 publications
1
112
0
4
Order By: Relevance
“…In turn, the abundance of potential pathogenic species such as Acinetobacter and Pseudomonas exhibited the opposite pattern. Interestingly, a recent study has reported that Pseudomonas aeruginosa, an opportunistic pathogen from CeD patients, may have proteolytic activity and could trigger a severe intestinal inflammation synergistically with gluten in experimental CeD models (Caminero et al, 2019). All in all, our study provides new insights into the human milk bacterial profile and its potential role in CeD onset in children in a prospective study for the first time.…”
Section: Discussionmentioning
confidence: 68%
“…In turn, the abundance of potential pathogenic species such as Acinetobacter and Pseudomonas exhibited the opposite pattern. Interestingly, a recent study has reported that Pseudomonas aeruginosa, an opportunistic pathogen from CeD patients, may have proteolytic activity and could trigger a severe intestinal inflammation synergistically with gluten in experimental CeD models (Caminero et al, 2019). All in all, our study provides new insights into the human milk bacterial profile and its potential role in CeD onset in children in a prospective study for the first time.…”
Section: Discussionmentioning
confidence: 68%
“…Perturbations of the gut microbiota (dysbiosis) and viral infections have been suggested to trigger the first hit of mucosal inflammation [20,21]. In this regard, a series of elegant experiments has provided some mechanistic insights showing that both gluten-and amylase-trypsin inhibitor-derived peptides generated by pathobiont species, such as Pseudomonas aeriginosa, are able to disrupt the epithelial barrier, to activate protease-activated receptors-2 signalling, and to recruit intraepithelial lymphocytes in sensitized mice with a susceptible genetic background [22,23]. Nonetheless, gut mucosa may also harbour gluten-degrading bacteria, such as Rothia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli can hydrolase shorter peptides (Francavilla et al 2017); however, bacilli and clostridia can destruct also larger molecules. The degradation products have to be carefully considered as it has been shown that proteases produced by some bacteria increase the immunogenicity of gluten peptides (Nistal et al 2016;Caminero et al 2019).…”
Section: Discussionmentioning
confidence: 99%